Development and validation of a microbiological assay for determination of chlorhexidine digluconate in aqueous solution - Flávia Angélica Másquio Fiorentino; Marcos Antonio Corrêa; Hérida Regina Nunes Salgado (Universidade de São Paulo, 2013)
Chlorhexidine (CHX) is a broad-spectrum antiseptic that is used in many topical pharmaceutical formulations. Because there is no official microbiological assay reported in the literature that is used to quantify CHX, this paper reports the development and validation of a simple, sensitive, accurate and reproducible agar diffusion method for the dosage of chlorhexidine digluconate (CHX-D) in an aqueous solution. The assay is based on the inhibitory effect of CHX-D upon the strain of Staphylococcus aureus ATCC 25923, which is used as the test microorganism. The design 3x3 parallel-line model was used. The results were treated statistically by analysis of variance (ANOVA), and they were excellent in terms of linearity (r = 0.9999), presenting a significant regression between the zone diameter of growth inhibition and the logarithm of the concentration within the range of 0.5 to 4.5%. The results obtained were precise, having relative standard deviations (RSD) for intra-day and inter-day precision of 2.03% and 2.94%, respectively. The accuracy was 99.03%. The method proved to be very useful and appropriate for the microbiological dosage of CHX-D in pharmaceutical formulations; it might also be used for routine drug analysis during quality control in pharmaceutical industries.